Religion and the COVID-19 Pandemic in Southern Africa - Sibanda, Fortune; Muyambo, Tenson; Chitando, Ezra (Routledge Studies on Religion in Africa and the Diaspora, 2022)
This book investigates the role of religion in the context of the COVID-19 pandemic in Southern Africa. Building on a diverse range of methodologies and disciplinary approaches, the book reflects on how religion, politics and health have interfaced in Southern African contexts, when faced with the sudden public health emergency caused by the pandemic. Religious actors have played a key role on the frontline throughout the pandemic, sometimes posing roadblocks to public health messaging, but more often deploying their resources to help provide effective and timely responses. Drawing on case studies from African indigenous knowledge systems, Islam, Rastafari and various forms of Christianity, this book provides important reflections on the role of religion in crisis response. This book will be of interest to researchers across the fields of African Studies, Health, Politics and Religious Studies.